Expanding the spectrum of mesenchymal neoplasms with NR1D1‐rearrangement. Issue 7 (16th March 2022) - Lacambra, Maribel D.; Antonescu, Cristina R.; Chow, Chit; Chiu, Wang Kei; Demicco, Elizabeth G.; Ferguson, Peter C.; Swanson, David; To, Ka‐Fai; Zhang, Lei; Dickson, Brendan C.
Abstract: Undifferentiated mesenchymal neoplasms can be morphologically subclassified based on cell shape; epithelioid tumors may be diagnostically challenging, particularly since they can show morphologic and immunohistochemical overlap with epithelial neoplasms. Following the recent report of an NR1D1::MAML1 gene fusion in an undifferentiated pediatric neoplasm, we performed a retrospective archival review and identified four additional cases of undifferentiated mesenchymal neoplasms with NR1D1 ‐rearrangement. All four tumors occurred in adult women. The tumors involved superficial and/or deep soft tissues of the extremities or abdomen. Morphologically, they showed a spectrum of overlapping features. In addition to epithelioid cells, two cases also had a prominent spindle cell component. Two cases also had admixed polygonal cells containing prominent cytoplasmic vacuoles with amorphous debris. The immunophenotype was nonspecific but all cases had at least focal keratin expression; this was extensive in two tumors. Targeted RNA‐sequencing revealed two cases each with NR1D1::MAML1 and NR1D1::MAML2 gene fusions. One patient developed lung and liver metastases, and one patient required amputation due to multifocal disease and underlying bone involvement. This study confirms undifferentiated NR1D1 ‐rearranged sarcoma represents a distinct mesenchymal neoplasm with an epithelioid morphology and potential for aggressive behavior. Further, we offer new insight into the spectrum of clinical, morphologic, immunohistochemical, and molecular findings possible in these rare neoplasms. An awareness of this entity is especially important given the potential for misclassification as a carcinoma.